THE PROFITABILITY ANALYSIS OF DAIRY CATTLE BUSINESS ON THE GROUP OF DAIRY FARMERS IN WEST UNGARAN DISTRICT SEMARANG REGENCY - Dolewikou, R. L.; Sumekar, W.; Setiadi, A. (Diponegoro University, 2016)
The objective of the study was to determine the profitability of dairy cattle business on the group of dairy farming in District of West Ungaran, Semarang Regency. This research was conducted from February to March 2016 through a survey method. Respondents in this study were lactating dairy farmers on the group of dairy farmers in District of West Ungaran. Then, location was determined by using purposive sampling. Further, respondents were determined by using census method for 40 people; those were 11 respondents of Mardi Mulyo farmer group members, 4 respondents of Sumber Hasil members, and 25 respondents of Ngudi Makmur members. Then, data were analyzed by employing the analysis of income and profitability. The result of study indicated that the average income over the cash cost was as much as IDR. 34,708,139.20 per year or IDR.2,892,344.93 per month, and the average income over the total cost was as much as IDR.4,867,808.92 per year or IDR. 405,650.74 per month. The profitability was 10.34% greater than the bank interest for farming business loans for 5% per year. It could be concluded that dairy cattle business on the group of dairy farmers in West Ungaran was profitable.